1992
DOI: 10.1128/jvi.66.2.632-640.1992
|View full text |Cite
|
Sign up to set email alerts
|

Novel GACG-hairpin pair motif in the 5' untranslated region of type C retroviruses related to murine leukemia virus

Abstract: We searched for the presence of common RNA structural motifs in mammalian type C retroviruses related to murine leukemia viruses and the closely related avian spleen necrosis virus. A novel motif consisting of a pair of hairpins, called hairpin pair motif, was detected in the 5' untranslated regions of the genomes of these retroviruses. A combination of computational analyses that included the assessment of phylogenetic sequence conservation by multiple alignment, the search for regions with unusual RNA foldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…This observation seems to hold for other retroviruses. Avian spleen necrosis virus contains in the 5Ј leader region a double hairpin which is conserved in several type C retroviruses (36) and involved in RNA packaging (59). It should also be noted that several HIV-1 motifs involved in packaging have been implicated in the process of dimerization (13,40,47), a finding consistent with the idea that these processes are linked (21,22).…”
Section: Discussionsupporting
confidence: 57%
“…This observation seems to hold for other retroviruses. Avian spleen necrosis virus contains in the 5Ј leader region a double hairpin which is conserved in several type C retroviruses (36) and involved in RNA packaging (59). It should also be noted that several HIV-1 motifs involved in packaging have been implicated in the process of dimerization (13,40,47), a finding consistent with the idea that these processes are linked (21,22).…”
Section: Discussionsupporting
confidence: 57%
“…No similar structure was identified by free energy studies on the analogous regions of SMRV or mouse mammary tumor virus. There are two GACG sequences at positions 788 to 794 which will form the stem-loop structure represented in panel C. This bears some resemblance to the motif identified by Konings et al (34). The biochemical data support the existence of this structure, but it is not conserved in SRV-2 and the free energy prediction is lower than those for the structures shown in panels A and B.…”
Section: Free Energy Minimizationsupporting
confidence: 60%
“…The GACG-hairpin motifs identified by Konings et al (34) occur in type C murine leukemia viruses and SNV (63). In the latter, linker-scanning mutagenesis showed that mutation of the GACG motif impairs packaging.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations